Variations in mesothelioma mortality rates among migrants to Australia and Australian-born. Issue 5 (4th July 2018) - Si, Si; Peters, Susan; Reid, Alison
ABSTRACT: Background: Australia's use and consumption of asbestos occurred at the same time as its immigration boom. Our objective was to investigate mesothelioma death rates among migrants and Australian-born between 1981 and 2012. Methods: Australian national mesothelioma deaths from 1981 to 2002 and 2006 to 2012 together with national censuses from 1981 to 2011 were extracted and combined. Directly standardised rates and negative binomial regression were applied examining differences in mesothelioma death rates with regard to country of birth. Results: Migrants from the UK and Ireland, Italy and Germany had significantly higher mesothelioma death rates than Australian-born; lower rates were observed among migrants from other countries. Conclusions: Our findings suggest there may have been differences in occupational health and safety between foreign and Australian-born. Because of changes in the demographics of migrants to Australia since the 1970s and changes in occupational circumstances over time, further comparisons of occupational-related health outcomes between foreign and Australian-born could identify potential occupational inequalities that may still exist today.